2015
DOI: 10.1039/c5ra15081g
|View full text |Cite
|
Sign up to set email alerts
|

Facile route to synthesis and morphology control of anionic waterborne polyurethane hollow microspheres via self-crosslinking reaction

Abstract: Porous waterborne polyurethane (WPU) hollow microspheres were synthesized via a self-crosslinking reaction of WPU prepolymer terminated by 3-aminopropyltriethoxysilane (APTES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…TEA was selected for further examination due to particle size and distribution as well as the suspected less hydrophilic network and more rapid release/degradation rates previously demonstrated in noncomposite porous SMPs . While the smallest size distribution was achieved with HPED ( D w / D n = 1.10), TEA at room temperature resulted in the smallest particle diameter, similar to those results reported by Kong and others using similar methods. , Results obtained by changing the temperature indicated that room temperature gave the smallest particle diameter of 2.43 ± 0.91 μm, a size that falls within the desired range for embolic applications and for particles that can be phagocytized by cells. , …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…TEA was selected for further examination due to particle size and distribution as well as the suspected less hydrophilic network and more rapid release/degradation rates previously demonstrated in noncomposite porous SMPs . While the smallest size distribution was achieved with HPED ( D w / D n = 1.10), TEA at room temperature resulted in the smallest particle diameter, similar to those results reported by Kong and others using similar methods. , Results obtained by changing the temperature indicated that room temperature gave the smallest particle diameter of 2.43 ± 0.91 μm, a size that falls within the desired range for embolic applications and for particles that can be phagocytized by cells. , …”
Section: Resultssupporting
confidence: 77%
“…11 While the smallest size distribution was achieved with HPED (D w /D n = 1.10), TEA at room temperature resulted in the smallest particle diameter, similar to those results reported by Kong and others using similar methods. 31,36 Results obtained by changing the temperature indicated that room temperature gave the smallest particle diameter of 2.43 ± 0.91 μm, a size that falls within the desired range for embolic applications and for particles that can be phagocytized by cells. 37,38 Poly(urethane) urea (PU) microparticles contain a thermoplastic polyurea core with the PU cross-linked shell surrounding it.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…[4][5][6] Several different structural PU microspheres have been prepared to expand its application, including solid microspheres, 7 nanoparticle coated microspheres 8 and porous/hollow microspheres. 6,9,10 During the last decade, polymer microspheres with hollow interiors displayed diverse applications, including encapsulation of drug compounds, protection of sensitive agents and adsorption of pollutants. [11][12][13][14][15] Compare to the hollow microspheres with solid surface, porous-hollow microspheres which possess low density and high specic surface area have aroused considerable amounts of interests in many application elds, such as adsorbents, 16 tissues engineering, 17 stimuli-responsive particles, 18 drug delivery, 19 and controlled release.…”
Section: Introductionmentioning
confidence: 99%